La gouvernance forestière au Québec : le défi du changement institutionnel dans les systèmes socio-écologiques interdépendants - Alain Fréchette (VertigO, 2009)
Quebec’s forestry sector is an a state of crisis. The reasons for this emerging tragedy include both conjunctural and structural elements. While the origins of this crisis are most often associated with the 1986 reform of the province’s forest regime, the history of forest resource governance in Quebec reveals that the problems affecting this sector are not new. In fact, the unsustainable nature of forest resource exploitation in Quebec and the sector’s vulnerability to sudden shifts in foreign commodity markets have always been at the forefront of concern to resource managers as well as social, political and economic actors within the province. However, in spite of ongoing calls for change over the last century to improve the sustainability of forest resource use and equity of socioeconomic outcomes, it appears as though the numerous changes enacted over the decades at the margin of succeeding forest regimes have yet to resolve the fundamental problems affecting this industry. When one considers the growing number of environmental dilemmas we now face at the onset of the 21st century (e.g., climate change, biodiversity loss, pollution, overexploitation of natural resources), what lessons can be drawn from the history of forestry in Quebec? In other words, why is it so difficult to change unsustainable governance institutions and resulting payoff structure once a regime becomes established?